2022
DOI: 10.1177/09718907221091717
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Retailers’ Behavioural Intentions Towards Using M-payment: Extending UTAUT with Perceived Risk and Trust

Ahmed Taher Esawe

Abstract: This study aims to identify the factors influencing retailers’ intentions to use m-payment. The Unified Theory of Acceptance and Use of Technology (UTAUT) model was adopted and extended with two additional variables: trust and perceived risk (PR). The sample of 682 respondents was obtained through an online survey distributed to retailers throughout Egypt. The partial least squares-structural equation modelling method was employed to analyse the data and test the hypotheses of this study. In terms of outcome, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…PR has been measured in consumer research and has most often been conceptualized as a multidimensional construct (Sun, 2014;Tingchi et al, 2013). Various studies in the past have confirmed the relationship between PR and behavioural intention (Bhat et al, 2021;Esawe, 2022;Mishra et al, 2022;Sweeney et al, 1999). Consumers associate several risks with shared luxury consumption like hygiene issues, product performance, quality concerns and lack of trust (Armstrong et al, 2015;Tussyadiah, 2015).…”
Section: Moderating Role Of Perceived Riskmentioning
confidence: 99%
“…PR has been measured in consumer research and has most often been conceptualized as a multidimensional construct (Sun, 2014;Tingchi et al, 2013). Various studies in the past have confirmed the relationship between PR and behavioural intention (Bhat et al, 2021;Esawe, 2022;Mishra et al, 2022;Sweeney et al, 1999). Consumers associate several risks with shared luxury consumption like hygiene issues, product performance, quality concerns and lack of trust (Armstrong et al, 2015;Tussyadiah, 2015).…”
Section: Moderating Role Of Perceived Riskmentioning
confidence: 99%
“…According to Esawe (2022), perceived risk has a significant impact on retailers' behavioral intentions to use mobile payments. Another study found a negative impact of PR on millennials' attitudes toward using m-payment (Zhu et al, 2022).…”
Section: Perceived Risk (Pr)mentioning
confidence: 99%